2006
DOI: 10.1038/nsmb1152
|View full text |Cite
|
Sign up to set email alerts
|

Rad4–Rad23 interaction with SWI/SNF links ATP-dependent chromatin remodeling with nucleotide excision repair

Abstract: Chromatin rearrangement occurs during nucleotide excision repair (NER). Here we show that Snf6 and Snf5, two subunits of the SWI/SNF chromatin-remodeling complex in Saccharomyces cerevisiae, copurify with the NER damage-recognition heterodimer Rad4-Rad23. This interaction between SWI/SNF and Rad4-Rad23 is stimulated by UV irradiation. We demonstrate that NER in the transcriptionally silent, nucleosome-loaded HML locus is reduced in yeast cells lacking functional SWI/SNF. In addition, using a restriction enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
145
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(148 citation statements)
references
References 32 publications
2
145
1
Order By: Relevance
“…This is expected since in vitro studies have suggested that SWI/SNF has an important role in chromatin remodeling and efficient NER of UV lesions (13,14). Studies in yeast as well as in mammalian cells also indicated that SWI/SNF is indispensable for NER (15,16). However, we found that Brg1 does not bind to another UV lesion 6-4PP and does not affect its repair.…”
Section: Brg1 Modulation Against Different Types Of Uv Lesions-wecontrasting
confidence: 48%
See 1 more Smart Citation
“…This is expected since in vitro studies have suggested that SWI/SNF has an important role in chromatin remodeling and efficient NER of UV lesions (13,14). Studies in yeast as well as in mammalian cells also indicated that SWI/SNF is indispensable for NER (15,16). However, we found that Brg1 does not bind to another UV lesion 6-4PP and does not affect its repair.…”
Section: Brg1 Modulation Against Different Types Of Uv Lesions-wecontrasting
confidence: 48%
“…Evidence from yeast has shown that SNF5 and SNF6, two subunits of SWI/SNF, interact with XPC on the chromatin and are involved in NER (15). To determine if Brg1 directly interacts with the core NER factor XPC in mammalian cells, HeLa-XPC cells were UV irradiated at 20 J/m 2 , and the soluble chromatin was immunoprecipitated with anti-HA affinity gel.…”
Section: Brg1 Interacts With Xpc and Its Recruitment To Cpd Depends Omentioning
confidence: 99%
“…For example, a direct interaction between Rad4/Rad23 and components of the SWI/SNF complex was suggested to load the SWI/SNF complex in aiding NER in budding yeast (37). Thus, generation of accessible DNA for lesion removal requires coordination of remodeling complexes with distinct catalytic functions.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in yeast revealed an enhanced association of subunits of the SWI/SNF chromatin-remodelling complex with Rad4-Rad23 (XPC-RAD23B in human), the principal DNA damage recognition factor in GG-NER [81]. Also histone acetyltransferases (HATs) are known to stimulate NER.…”
Section: Recruitment Of Chromatin Remodellers In Tc-nermentioning
confidence: 99%